NOWCASTING, FORECASTING AND WARNING FOR IONOSPHERIC PROPAGATION: TOOLS AND METHODS - Stamper R.; Cander L.R.; Belehaki A.; Tsagouri I.; Burešová D.; Kutiev I.; Pietrella M.; Zolesi B.; Stanisławska I.; Stankov S.; Tulunay Y.K. (My University, 2004)
The paper reviews the work done in the course of the COST 271 Action concerned with the development of tools and methods for forecasting, nowcasting and warning of ionospheric propagation conditions. Three broad categories of work are covered. First, the maintenance and enhancement of existing operational services that provide forecast or nowcast data products to end users; brief descriptions of RWC Warsaw and the STIF service are given. Second, the development of prototype or experimental services; descriptions are given of a multi-data source system for reconstruction of electron density profiles, and a new technique using real-time IMF data to forecast ionospheric storms. The third category is the most wide-ranging, and deals with work that has presented new or improved tools or methods that future operational forecasting or nowcasting system will rely on. This work covers two areas – methods for updating models with prompt data, and improvements in modelling or our understanding of various ionospheric-magnetospheric features – and ranges over updating models of ionospheric characteristics and electron density, modelling geomagnetic storms, describing the spatial evolution of the mid-latitude trough, and validating a recently-proposed technique for deriving TEC from ionosonde observations.